Security for Virtualization in Cloud Services using Duplication Method - N.L. Udaya Kumar; M. Siddappa (Institute of Advanced Engineering and Science, 2017)
Cloud computing is the way of computing, where all the computing resources are available as a service over the internet based on requirements of the users. Virtualization is the concept which plays very important role in reducing the cost of investment and increases utilization and allows multi-tenancy. This concept helps to create virtual resources out of existing physical resources. When the virtual resources are created, they may face the problems due to various reasons and may not work properly. Providing the protection to these virtual resources and make them to work without any problem is the important. Here we introduce an approach called duplication method which allows the users to create more number of same virtual resources, so that if one of the resources fail due to some reason, users may have some more same resources to continue without disturbing their work and provide the security at different levels to make Virtual resources secure.